PENGEMBANGAN KEMAMPUAN SUMBERDAYA MANUSIA DI LINGKUNGAN DINAS KELAUTAN DAN PERIKANAN PROVINSI KALIMANTAN TIMUR - Suwanti . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
Primary focus of this research is the development of human resources which incudes : the scintific development of (formal education) training education and training development of (non formal education) and trainig education adminitration, and tachnical training in the areas of leadership education and training, then transfer the mutation as well as career development promotion. Based of the results of reserach show that the increase in formal education in the scope of the department of Marine and Fisheries of East Kalimantan Province has been done so well on the development of (education and training/non-formal) only in the field of education and training of leadership has not been fully implemented to the fullest.